IMPACT OF BAZIAN CEMENT FACTORY ON AIR, WATER, SOIL, AND SOME GREEN PLANTS IN SULAIMANI CITY-IRAQ - & et al., AL-Taay (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out to assess impacts of industrial activities on environmental quality in Bazian cement factory, Sulaimani. Environmental impact of factory was carried out from September 2015 to August 2016 at studied area located at north west of city with coordinates of 35º36’242"- 045º04’470".Pollutant particles can have as consequence reduction of biodiversity and quality of water, soil and whole ecosystems. Especially, cement dust can be emitted at every stage of cement production which affects on photosynthetic process, leaf stomata, discoloration, enzymatic malfunction, growth reduction and productivity of plants. In this study, water, soil, air and three plants (Platycladus orientalis , Eucalyptus spp. and Melia azedarach) samples were collected. Ten water sources including 6 wells, 3 tanks and control in and around factory were selected in order to evaluate some physicochemical characteristics of water. Concentrations of some heavy metals including cadmium, chromium, lead, copper, nickel, iron and zinc were determined to evaluate pollution status. Soil samples include twelve different sites nine of them are cement dust exposed with three control sites. Same work for them had done. Heavy metal analysis and chlorophyll content for plants also determined. Air gases results had taken online from computer fixed on main stack monthly. Also dust from main stack had collected and analyzed for physicochemical parameters and heavy metals. Results showed that were within normal standards.